Brain‐Inspired Structural Plasticity through Reweighting and Rewiring in Multi‐Terminal Self‐Organizing Memristive Nanowire Networks. (19th August 2020) - Milano, Gianluca; Pedretti, Giacomo; Fretto, Matteo; Boarino, Luca; Benfenati, Fabio; Ielmini, Daniele; Valov, Ilia; Ricciardi, Carlo
Abstract : Neuromorphic Systems In article number 2000096, Daniele Ielmini, Ilia Valov, Carlo Ricciardi, and co‐workers report a brain‐inspired complex system based on self‐organizing memristive nanowire networks with functional connectivity that exhibit structural plasticity including rewiring and reweighting effects. These neuromorphic systems allow the realization of neural networks with heterosynaptic plasticity able to learn and adapt when subjected to external stimuli, emulating the experience‐dependent plasticity of the nervous system.